Imaging lung perfusion - Hopkins, Susan R.; Wielpütz, Mark Oliver; Kauczor, Hans-Ulrich (Journal of applied physiology, 2012)
From the first measurements of the distribution of pulmonary blood flow using radioactive tracers by West and colleagues (J Clin Invest 40: 1-12, 1961) allowing gravitational differences in pulmonary blood flow to be described, the imaging of pulmonary blood flow has made considerable progress. The researcher employing modern imaging techniques now has the choice of several techniques, including magnetic resonance imaging (MRI), computerized tomography (CT), positron emission tomography (PET), and single photon emission computed tomography (SPECT). These techniques differ in several important ways: the resolution of the measurement, the type of contrast or tag used to image flow, and the amount of ionizing radiation associated with each measurement. In addition, the techniques vary in what is actually measured, whether it is capillary perfusion such as with PET and SPECT, or larger vessel information in addition to capillary perfusion such as with MRI and CT. Combined, these issues affect quantification and interpretation of data as well as the type of experiments possible using different techniques. The goal of this review is to give an overview of the techniques most commonly in use for physiological experiments along with the issues unique to each technique.